(untitled) (American Journal of Islam and Society, 2009)
Most studies on the epic events in Karbala and the martyrdom in 680 of Husayn, the Prophet’s grandson, have focused on the possible ramifications of his sacrifice and the paradigmatic models that can be constructed from this event. Other studies have examined the various genres of Shi`i rituals enacted to commemorate Husayn’s martyrdom. Akbar Hyder’s Reliving Karbala examines this death from very different perspectives. The author does not claim to provide a systematic exposition of the historical events or philosophy of Husayn’s martyrdom. He neither focuses on the written texts of history nor presents a normative reading of Karbala. Rather, he transcends the traditional Shi`i-coded understanding by offering a more trans-sectarian and trans-communal, as well as multiple readings, of this entire episode. The book also covers Karbala’s influence on the South Asian cultural and literary landscape, demonstrating, in the process, how this narrative is appropriated and lived in the contexts and memories of South Asian Muslims and non-Muslims at different times. Hyder uses a wide array of sources, ranging from classical Islamic texts to modern twentieth-century discourses and incorporates citations from Iqbal, Premchand, Gandhi, and others. The book opens a window on how various interpretive strategies can be utilized to read a seventh-century event and how they can shape social milieus inhabited by more than a billion people ...